Unveiling Pelvic Floor Health: Understanding Awareness, Perspectives and Habits in Pakistani Women of Reproductive Age : Unveiling Pelvic Floor Health - Ismail, Ayesha; Bibi, Iqra (Pakistan Journal of Health Sciences, 2024)
The pelvic floor, a crucial anatomical structure supporting pelvic organs, is vital in various physiological functions. Pelvic Floor Dysfunction (PFD) encompasses disorders affecting pelvic floor muscles and is a significant health concern globally. Pelvic floor muscle training (PFMT) has been advocated for managing PFD, especially in women post-childbearing. However, there is a lack of awareness and understanding regarding PFMT in Pakistani women. Objective: To assess the Knowledge, Attitude, and Practice (KAP) towards PFMT among women of childbearing age in a rural health centre in Haripur, Pakistan. Methods: A cross-sectional study was conducted at a Rural Health Center in Haripur, Pakistan, involving 158 women aged 20 to 50. A structured questionnaire covered KAP's details regarding PFMT. Data analysis employed SPSS 26.0, utilizing mean and standard deviation. Results: The study revealed a response rate of 52.6%, with a mean age of 30±7.3 years for participants. Notably, 29.1% of women reported an inability to control their urine. Knowledge assessment showed that 54.9% of participants knew pelvic exercises and their potential benefits. Attitude towards PFMT was positive in 41.8% of women, while only 20.5% practised PFMT regularly. Pregnant women exhibited a higher prevalence of urinary incontinence. Conclusions: The study concludes that a substantial proportion of women in Pakistan lack awareness of PFMT benefits, leading to inadequate practice. This underscores the importance of implementing awareness programs and training sessions targeting women of childbearing age to address the challenges posed by PFD effectively.